Characterization of bi-layers formed over maraging steel 300 during aging process with steam atmosphere by GIXRD and SEM - Vanessa Sanches Pereira da Silva; José Roberto Ferreira Neto; Silvia Lucas Ferreira da Silva; Diogo Costa de Oliveira; Fábio de Camargo (Brazilian Journal of Radiation Sciences, 2021)
Maraging steels are martensitic steels hardened by precipitation during thermal aging, with good machining properties and high strength and corrosion resistance. It is well suited for applications which require high strength-to-weight material, being used in aerospace, aeronautics and nuclear industries. A protective and corrosion resistant oxide layer can be formed during age hardening if treated in steam atmosphere. This work aims to use grazing incidence X-ray diffraction (GIXRD) to evaluate qualitatively the thickness of the layers formed during this process. GIXRD and scanning electron microscopy (SEM) were employed to identify and order the layered structure formed on four specimens of maraging steel grade 300 with different surface finishes that were previously solution annealed twice at (950 ± 5) °C for 1 h, air-cooled, and submitted to oxidation process under positive pressure around 1.5 kPa of steam at (480 ± 5) °C for 6 h followed by forced air cooling. The diffraction patterns were measured employing CuKα radiation and parallel beam, in step scan mode, using incident angles varying from 0.2º to 4.0º and 20º < 2θ < 85º. The results revealed the formation of two layers, the innermost was formed by γ-iron (austenite – fcc) phase followed by a mixture of oxides (hematite and magnetite) on the top, regardless of surface finish, which was confirmed by the SEM analysis that also allowed the measurement of the average layer’s thickness of oxides (1.130 ± 0.094) µm and austenite (0.507 ± 0.090) µm phases, and corroborated the qualitative thicknesses analysis made from GIXRD results.